Proteolytic enzyme and adiponectin receptors as potential targets for COVID-19 therapy - K. A. Rubina; N. R. Sabitova; A. Yu. Efimenko; N. I. Kalinina; J. A. Akopyan; E. V. Semina (Кардиоваскулярная терапия и профилактика)
The coronavirus disease 2019 (COVID-19) pandemic requires not only the creation of vaccines to prevent the spread of the disease, but also the development of novel drugs aimed at reducing viral load, suppressing an excessive immune response and preventing the severe complications such as lung fibrosis and acute respiratory distress syndrome. One of the promising targets for studying the development of pneumonia, systemic inflammation and disseminated intravascular coagulation in COVID-19 is the plasminogen activator system. In patients with a severe disease course, impaired activity or expression of plasminogen activators significantly increases the blood level of D-dimer and fibrinogen, as well as correlates with intravascular coagulation and thrombus formation. The second promising target for studying the pathogenesis of COVID-19 is the adiponectin/T-cadherin system: adiponectin is able to reduce the content of pro-inflammatory cytokines, the increase of which is characteristic of COVID-19, and stimulate the production of an anti-inflammatory cytokine interleukin-10. The review describes the role of plasminogen and T-cadherin activators in their possible participation in the development of pulmonary fibrosis in COVID-19 and hemostasis regulation, as well as cardio- and vasculoprotective function of adiponectin and its receptor, T-cadherin.